Observational pilot using a Data to Care intervention strategy to promote HCV re-engagement and cure for persons with HIV/HCV co-infection who are out of care - Maximilian Wegener; Deborah Gosselin; Ralph Brooks; Suzanne Speers; Merceditas Villanueva (BMC Health Services Research)
Abstract Background With Direct Acting Antivirals for Hepatitis C virus (HCV), cure is possible in > 95% including those with HIV/HCV co-infection. Achieving strategic targets for cure requires addressing barriers including suboptimal care engagement. We adapted Data to Care (D2C), a public health strategy designed to identify and link persons out of care (OOC) for HIV, for persons with HIV/HCV co-infection untreated for HCV. Methods In partnership with Connecticut Department of Public Health (DPH), persons OOC for HIV (defined as no HIV surveillance laboratory tests from 10/1/2018–10/1/2019) were matched to a list of persons co-infected with HIV/HCV (through 12/31/2019). We used a three-phase follow-up approach (pre-work, case conferencing, and Disease Intervention Specialist (DIS) follow-up) to track outreach outcomes and re-engagement/HCV cure success. Results There were 90 HIV/HCV co-infected persons who were OOC for HIV. The pre-work and case conferencing phases determined that 33 (36.7%) had previous HCV cure or were in treatment. There were 41 eligible for DIS-follow-up of which 21 (51%) were successfully contacted and 7 (33%) successfully re-engaged (kept appointment with HCV provider). No new HCV treatment initiations were recorded. Conclusions Using a D2C approach, we identified and conducted outreach to persons who were OOC for HIV to promote HCV treatment. This approach resulted in intensive data clean-up and outreach efforts which produced modest re-engagement and no HCV treatment initiations. Future studies should develop alternative and complementary interventions to promote effective re-engagement and HCV treatment.